An Analysis on Serious Incidents and Accidents in Aviation Using Shell Model - Pangsa Rizkina Aswia; Dwi Lestary; Firdaus Masykur; Gilang Trio Putra (WARTA ARDHIA, 2022)
A thorough investigation must be conducted in every aviation incident or accident to find the root cause so that recommendations can be drawn to prevent the same incident or accident from occurring again. This research is a descriptive analysis with quantitative methods. Data were collected from the final reports released by the KNKT from 2015 until 2019. The main causes were grouped using the SHELL Model analysis. The results showed that the most prevalent cause of aviation incidents/accidents in Indonesia was the mismatch between liveware-liveware of which the percentage reached 64%. Furthermore, this mismatch was caused by lack of supervision from management as many as 17 events or 74%; 5 events or 22% were caused by unavailability of rules; and lack of coordination with as many as 1 event or 4%. Within 17 events caused by lack of supervision from management, there were 3 phases of which the events occurred namely the landing phase comprising 59% or 10 events, the cruising phase comprising 18% or 3 events, and the approaching phase consisting of 24% or 4 events. Accidents and serious incidents may occur if latent causes such as lack of supervision from management, unavailability of rules and lack of coordination are not mitigated.